The Role of Education in Building Climate Change Awareness Among the Younger Generation - Alfrid Sentosa; Asro Laelani Indrayanti; Elyta Vivi Yanti; Yos Andy Tangkasiang (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Climate change is an urgent global challenge and affects life all over the world. The young generation as the nation's successors has an important role in dealing with this issue. The aim of this research is to understand how education can contribute to increasing awareness of climate change among the younger generation. This research also aims to identify the most effective educational methods in conveying information about climate change. The method used in this research is a qualitative approach. Researchers conducted a survey of 150 students from various levels of education, from elementary school to college. In addition, in-depth interviews were conducted with 15 educators who teach material related to the environment and climate change. The data obtained was then analyzed to identify emerging patterns and themes. This research also considers local and global contexts in understanding the impact of education on climate change awareness. The results showed that 75% of students who participated in environmental education programs had a better understanding of climate change compared to those who were not involved in the program. In addition, 60% of students stated that they felt motivated to contribute to climate change mitigation efforts after participating in relevant educational activities. Educational programs that involve hands-on practice, such as tree planting and waste management activities, have proven to be more effective in building student awareness and engagement.